“It Has Totally Changed How I Think About the Police”: COVID-19 and the Mis/Trust of Pandemic Policing in Aotearoa New Zealand - Deckert, Antje (Criminal justice review, 2024)
In the initial phase of COVID-19, Aotearoa New Zealand was internationally praised for its pandemic response that included lockdowns to control the spread and work toward elimination. Community compliance with control measures was thus essential when pursuing elimination as a policy. Using a mixed-methods approach, we sought to explore whether New Zealand Police (NZP) were trusted to police the lockdown rules at Levels 4 and 3. We analyzed 1,020 survey responses comparing trust among respondents who had been stopped by NZP over the lockdown rules (contacts) with those who had not (non-contacts). We found that both contacts and non-contacts expressed greater trust in NZP to enforce the Level 4 than the Level 3 rules; contacts expressed less trust in NZP to enforce the lockdown rules than non-contacts; contacts perceived NZP more heavy-handed than non-contacts; contacts perceived NZP as only somewhat procedurally just and feeling somewhat encouraged to comply with the lockdown rules and; that unexpected high-profile policing-related events during the survey only affected contacts’ trust significantly. We offer two explanations: (1) NZP were perceived as procedurally unjust or inconsistent in applying the lockdown rules, (2) members of the public and NZP learned the lockdown rules simultaneously. We caution that the unfamiliar character of pandemic policing may jeopardize trust in NZP even among segments of the population that typically express high levels of trust in NZP, that is, people of European descent. We conclude that community compliance with pandemic control measures is no matter to be dealt with by the criminal legal system.